Three-dimensional nature of the glottal jet - Triep, Michael; Brücker, Christoph (The Journal of the Acoustical Society of America, 2010)
The factors contributing to human voice production are not yet fully understood. Even normal human phonation with a symmetric glottal opening area is still the subject of extensive investigation. Among others, it has already been shown that fluid dynamics has a strong influence on the vocal process. The full characterization of the glottal jet has not been accomplished yet. Time-resolved measurement and visualization of the three-dimensional (3D) flow downstream the human vocal folds are difficult if not impossible to perform in vivo. Therefore, it is common to use mechanical and numerical models with a simplified shape and motion profile of the vocal folds. In this article, further results regarding the 3D flow structure obtained in a 3:1 up-scaled dynamic glottis model (cam model) in a water circuit are given, extending earlier work [M. Triep et al. (2005). Exp. Fluids 39, 232-245]. The model mimics the temporal variation in the 3D contour of the glottal gap while water flow reduces the characteristic frequencies by the order of 1/140. The unsteady flow processes downstream of the vocal folds are visualized in slow motion and analyzed in detail via particle imaging techniques. The visualization results show complex 3D flow behavior of lengthwise jet contraction and axis switching. In addition, the time-dependent flow rate during the phonatory oscillation cycle is measured in detail. It is shown that the pressure loss is decreased in the presence of a second constriction downstream of the glottis in form of ventricular folds and it is observed that for this case the jet is stabilized in the divergent phase of the cycle.